The European Initiative ProYouth for the promotion of mental health and the prevention of eating disorders* screening results in Hungary - Szabó, Kornélia; Czeglédi, Edit; Babusa, Bernadett; Szumska, Irena; Túry, Ferenc; Sándor, Imola; Bauer, Stephanie (European eating disorders review, 2015)
Objective The ProYouth programme focuses on the promotion of mental health and the prevention of eating disorders (EDs) among young people. The aim of our study was to explore whether the programme can address individuals who are at risk for developing 2EDs. Method This study is designed as an online cross-sectional survey (n = 664, 12.2% men, 87.8% women, mean age: 24.9 years, SD = 5.4 years, range: 18-40 years). Measures included demographic data, self-reported weight and height, the Patient Health Questionnaire for Depression and Anxiety, Short Evaluation of Eating Disorders, Weight Concerns Scale and previous/current treatment for EDs. Results In terms of severity of EDs, 22.9% (n = 152) of the screened participants were symptom free, 48.8% (n = 324) had considerable concerns about their weight, 11.1% (n = 74) were slightly impaired, 15.1% (n = 100) had severe impairment and 2.1% (n = 14) of participants are currently under treatment for EDs. In total, 56.3% of users (n = 374) registered in the programme. According to our results, those who had considerable concerns about their weight and individuals who were severely impaired registered with a greater odds to the programme than those who were symptom free [odds ratio (OR) = 1.64, p = .021 and OR = 1.90, p = .023, respectively]. Furthermore, those who previously received treatment for their ED registered to the programme with greater odds than those who did not (OR = 2.40, p = .017). Conclusion ProYouth successfully addressed those who have elevated concerns about their weight and who also registered with greater odds to the programme than those who were symptom free regarding EDs. The screening results show that there is a greater need for specialized care targeting EDs in Hungary than what is currently available. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.
Gesehen am 25.06.2020